The Effect Of Mung Bean Extract And Iron Tablets On Hemoglobin Levels Among Female Adolescents At Sman 9 South Singkawang, West Kalimantan - Askiah; Putri Azzahroh; Bunga Tiara Carolin (Rajaki of Tulip Medika Publisher, 2026)
Background: Adolescence is characterized by increased iron requirements, while anemia remains prevalent among female adolescents, with rates of 48.9% nationally (Riskesdas 2018), 25.77% in Singkawang City (2024), and 7.01% at SMAN 9 South Singkawang. Anemia prevention includes iron tablet supplementation and mung bean juice consumption to support hemoglobin formation. Purpose: To analyze the effect of mung bean juice and iron tablet supplementation on hemoglobin levels among female adolescents at SMAN 9 South Singkawang, West Kalimantan. Methods: This study employed a quasi-experimental design with a pretest–posttest two-group approach. The sample consisted of female adolescents selected using a random sampling technique. Participants were divided into two groups: the control group received mung bean juice, while the intervention group received a combination of mung bean juice and iron tablet supplementation. With a total sample of 54 respondents. Paired t-test was used to analyze the effect within groups, and independent t-test was applied to compare the effects between groups. Results: The mean hemoglobin level in the intervention group increased from 12.3 g/dL to 13.5 g/dL, while in the control group it increased from 12.0 g/dL to 12.9 g/dL. There was a significant increase in hemoglobin (Hb) levels in both groups after the intervention (p < 0.000), and the combination of mung bean juice and iron tablet supplementation was more effective than mung bean juice alone (p = 0.005). Conclusion: The combination of mung bean juice and iron tablet supplementation was clinically effective and statistically significant in increasing hemoglobin levels among female adolescents compared to mung bean juice alone.